Formative Assessment: Tertiary Student Perceptions - Hurst, Chris (AARE, 2011)
It is often suggested that formative assessment should be the preferred mode of diagnostic assessment in all levels of education. Formative assessment is generally considered to constitute evaluation within educational programs while students are still learning, and it has many perceived benefits. However, formative assessment is perhaps not used as widely as it might be, possibly because it is not broadly practiced in the tertiary sector. The study described in this paper is based on a 'transformative assessment' model, the intention of which is to change teacher practice and student learning habits. This paper reports on an interpretive study that investigated the perceptions and attitudes towards formative assessment of a first year cohort of pre-service teachers while they studied a core unit in their Bachelor of Education program that was taught and assessed using a transformative assessment model. Data were generated from a questionnaire administered to the entire student cohort, as well as from semi-structured interviews conducted with a small sample of students. Data were then coded and sorted into emergent themes.The study concluded that students generally favoured formative approaches with particular reference to constructive feedback and peer reviewing, though there were reservations expressed about factors which compromised the quality of peer reviewing. Personal reflection was seen as a useful component of the overall assessment, but it was not necessarily reliable. Thus, the implementation of the formative assessment process, including the development of relevant skills, was seen as critical.